(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. La centralità del consenso nel matrimonio canonico – 2. I presupposti cognitivi dell’electio matrimonii nella dottrina tomistica – 3. Il defectus debitae cognitionis nella tradizione classica: la diversa rilevanza dell’error substantialis e dell’error contra substantiam matrimonii - 4. I defectus consensus ex parte intellectus come defectus discretionis iudicii - 5. La duplicazione delle figure del defectus debitae cognitionis nel codice piano-benedettino – 6. Problemi di compatibilità tra l’ignorantia in re matrimoniali e altre fattispecie giuridiche – 7. L’ampiezza della scientia minima - 8. Le modifiche della legislazione giovanneo-paolina: la debita cognitio - 9. L’error determinans voluntatem - 10. Verso una nuova comprensione del defectus debitae cognitionis: questioni aperte sulla scientia minima - 11. Defectus cognitionis o defectus discretionis iudicii? Reflections on ignorantia in re matrimoniali: a canon still relevant? ABSTRACT: The paper examines the origin of the canon on ignorantia in re matrimoniali, introduced by the 1917 Code of Canon Law, comparing it with the psychological presuppositions of scholastic doctrine that inspire the canonical discipline on matrimonial consent and with the consolidated principles in the canonical tradition about the relevance of the lack of debita cognitio in the spouses. Given that the canon has been preserved in the current legislation, critical remarks are raised regarding the consistency with the conception of matrimonial consent as an act of the person, and it is proposed to change the approach of the case of invalidity, from defectus cognitionis to defectus discretionis iudicii.